The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1078155217735688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the head and neck cancer patient population and the incidence of hospitalization at an academic medical center

Abstract: Purpose Patients with head and neck cancer are at risk for disease- and treatment-related toxicities that may be severe enough to require hospitalization. The risk factors associated with hospitalization in these patients are not well defined. Methods We conducted a single-center, retrospective observational study of patients with head and neck cancer receiving chemotherapy at an academic medical center infusion clinic in a one-year period. The primary objective was to characterize the head and neck cancer pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Alcohol dependence and abuse has been shown to be an independent risk factor of poor outcomes in head and neck cancer surgery patients. 25 In their evaluation of adult patients following oral and maxillofacial surgery, Loeffelbein et al 26 found that alcohol abuse was an independent risk factor of postoperative pulmonary complications. Alcohol dependence and abuse is associated with liver disease, and such liver pathology may increase in the risk of poor postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol dependence and abuse has been shown to be an independent risk factor of poor outcomes in head and neck cancer surgery patients. 25 In their evaluation of adult patients following oral and maxillofacial surgery, Loeffelbein et al 26 found that alcohol abuse was an independent risk factor of postoperative pulmonary complications. Alcohol dependence and abuse is associated with liver disease, and such liver pathology may increase in the risk of poor postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[34]. The examination by Hazelden et al, 2019, identified a few factors which might be helpful to recognize patients as high risk for hospitalization and the following stages will be to decide and consider the role of the drug specialist in preventing hospitalization of these patients [35]. However, machine learning based drug synergy prediction approaches suffer from the parameter tuning problem.…”
Section: Related Workmentioning
confidence: 99%
“…2 Since the majority of patients often present with locally advanced disease, multi-modality treatment is typically required and may include surgery, radiation, and/or systemic therapy. 1,4,5 As a result, HNC treatment is associated with significant toxicities, such as severe mucositis, odynophagia, dysphagia, dehydration, emesis, and poor oral intake. 4,5 It is well established that these toxicities can become severe enough to warrant hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 As a result, HNC treatment is associated with significant toxicities, such as severe mucositis, odynophagia, dysphagia, dehydration, emesis, and poor oral intake. 4,5 It is well established that these toxicities can become severe enough to warrant hospitalization. 4,5 Therefore, HNC treatment necessitates a multidisciplinary approach to ensure timely and coordinated care throughout treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation